Система запобігання та виявлення академічного плагіату серед здобувачів вищої освіти в ТДАТУ - Кюрчев, Володимир Миколайович; Кюрчев, Владимир Николаевич; Kiurchev, Volodymyr; Ломейко, Олександр Петрович; Ломейко, Александр Петрович; Lomeiko, Oleksandr (ТДАТУ, 2017)
Uk: В статті наведені результати аналізу та апробації існуючих програм антиплагіату для перевірки курсових і дипломних робіт (проектів) та шляхи впровадження ефективної системи запобігання та виявлення академічного плагіату серед здобувачів вищої освіти в ТДАТУ. En: In the article the brought results over of analysis and approbation of the existent programs of antiplagiarism for verification of term and diploma papers (projects) and ways of introduction of the effective system of prevention and exposure of academic plagiarism among the bread-winners of higher education in TSATU.
The system prevention and exposure of academic plagiarism is among bread-winners of higher education in TSATU
Keywords: плагіат; академічний плагіат; антиплагіат; компіляція; здобувач вищої освіти; автор; курсова робота; дипломна робота; проект; цитата; оригінальність тексту; plagiarism; academic plagiarism; antiplagiarism; compiling; bread-winner of higher education; author; term paper; diploma work; project; quotation; originality of text